COMMUNICATIVE COMPETENCE IN THE DEVELOPMENT OF STUDENTS’ PERSONAL AND PROFESSIONAL QUALITIES – AS A PEDAGOGICAL NECESSITY - Babaeva Gulnozakhon Latibjonovna (Bright Mind Publishing, 2025)
This article analyzes the role and importance of communicative competence in the development of students’ personal and professional qualities. It also highlights the pedagogical necessity of developing communicative competence in the modern educational process, discusses effective teaching methods, and examines the efficiency of communicative approaches and technologies in education.
Keywords: Communicative competence, personal qualities, professional skills, communication culture, educational technology, pedagogical process.